The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5851/kosfa.2014.34.5.665
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Culture, Conventional and Real-time PCR Methods for Listeria monocytogenes in Foods

Abstract: We compared standard culture methods as well as conventional PCR and real-time PCR for the detection of Listeria monocytogenes (L. monocytogenes) in milk, cheese, fresh-cut vegetables, and raw beef that have different levels of background microflora. No statistical differences were observed in sensitivity between the two selective media in all foods. In total, real-time PCR assay exhibited statistically excellent detection sensitivity (p<0.05) and was less time consuming and laborious as compared with standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…The average level of background microflora of the 82 beef samples was 4.53±2.67 log CFU per gram, suggesting that the real-time PCR assay could detect the targeted organism even when it was hidden by other background organisms in the culture media. The same phenomenon was observed in the real-time PCR assays for the detection of Listeria monocytogenes and Lactobacillus kefiranofaciens in food samples with high levels of background microflora (10,19). In addition, the results of the real-time PCR assay for detection of C. perfringens could be obtained within 30 h, whereas the conventional culture method requires 96 h (Fig.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The average level of background microflora of the 82 beef samples was 4.53±2.67 log CFU per gram, suggesting that the real-time PCR assay could detect the targeted organism even when it was hidden by other background organisms in the culture media. The same phenomenon was observed in the real-time PCR assays for the detection of Listeria monocytogenes and Lactobacillus kefiranofaciens in food samples with high levels of background microflora (10,19). In addition, the results of the real-time PCR assay for detection of C. perfringens could be obtained within 30 h, whereas the conventional culture method requires 96 h (Fig.…”
Section: Resultssupporting
confidence: 66%
“…The culture method is regarded as the standard method for the detection of C. perfringens from food samples, but it is timeconsuming and labor-intensive (9). Furthermore, the detection performance of this method can be profoundly diminished by the presence of competing flora in foods (10). To overcome these drawbacks, we previously developed a real-time PCR assay for the detection and enumeration of C. perfringens in foods (9).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the result of real-time PCR was obtained in 2 days, while the traditional method took 4-8 days [24]. Another study comparing standard culture methods, conventional PCR, and real-time PCR for the detection of Listeria monocytogenes in milk, cheese, fresh vegetables, and raw meat showed that the real-time PCR assay was statistically more sensitive, reducing the time of analysis and laborious work [25]. The targeted gene coding for a protein of the ribosome large subunit was used in qPCR for quantifying Enterobacteriaceae in 51 food products naturally contaminated.…”
Section: Qpcr Versus Traditional Culture Methods In Food Microbiologymentioning
confidence: 99%
“…All samples were purchased from a local grocery store in Seoul, Korea and were found to be free of C. sakazakii by standard culture methods. A plate count of the background flora of each food type was conducted as described earlier (9)(10)(11).…”
Section: Methodsmentioning
confidence: 99%